Penerapan Guru Dalam Mengembangkan Multiple Intelligences pada Masa Covid 19 di Kelas IX MTs Al-Ikhlas Pangkalan Susu - Satria Wiguna; Nadya Farhaini (As-Syar'i: Jurnal Bimbingan & Konseling Keluarga, 2020)
Various kinds of intelligence based on the development of students, it is believed that every student is born with more than one talent. Every student has talent, namely the ability that stands out in one aspect of personality, which is obtained as an innate. Therefore, since birth, every student is not stupid, there are children who are intelligent in different aspects. This type of research is qualitative research, data collection techniques by means of observation, interviews and documentation. Data analysis technique with reduction stage, data presentation stage and conclusion drawing. The results of the study found that the application of teachers in developing multipple intelligences in class IX students of MTS Al Ikhlas Pangkalan Susu was very good, although not perfect and had not yet achieved educational goals that were in accordance with covid learning and distance learning, learning methods and strategies that used various teachers, in order to teachers develop multiple intelligences during a pandemic. The factors supporting teachers in developing multiple intelligences include 1). Human Resources, 2) The intelligence of students in doing assignments, 3). Student interest in learning. 4). Supporting facilities. While the inhibiting factors are: the lack of channeling of student potential and the way to overcome it is to provide additional hours, improve the quality and competence of teachers and provide certificates of appreciation to students who excel.